2017
DOI: 10.1039/c7tc01166k
|View full text |Cite
|
Sign up to set email alerts
|

Strong ferroelectric polarization of CH3NH3GeI3 with high-absorption and mobility transport anisotropy: theoretical study

Abstract: The sub-band gap absorption in the ferroelectric lead-free hybrid perovskite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 59 publications
5
52
0
Order By: Relevance
“…Similarly, the bandgaps of 0.89 eV (PBEsol) and 1.1.17-1.61 eV (PBE) (Lu et al, 2016;Sun P.-P. et al, 2016;Zhao Y.-Q. et al, 2017) were reported for CH 3 NH 3 GeI 3 , and those of the hybrid functional range from 1.70 to 2.04 eV (Sun P.-P. et al, 2016;Zhao Y.-Q. et al, 2017), whereas the experimental value for which is 1.90 eV (Stoumpos et al, 2015).…”
Section: Optical Propertiesmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, the bandgaps of 0.89 eV (PBEsol) and 1.1.17-1.61 eV (PBE) (Lu et al, 2016;Sun P.-P. et al, 2016;Zhao Y.-Q. et al, 2017) were reported for CH 3 NH 3 GeI 3 , and those of the hybrid functional range from 1.70 to 2.04 eV (Sun P.-P. et al, 2016;Zhao Y.-Q. et al, 2017), whereas the experimental value for which is 1.90 eV (Stoumpos et al, 2015).…”
Section: Optical Propertiesmentioning
confidence: 65%
“…For example, the reported PBE bandgap for Cs 2 AgInCl 6 is 0.95 eV (Kumar et al, 2020), compared to the experimental value of 3.3 eV (Volonakis et al, 2017). Similarly, the bandgaps of 0.89 eV (PBEsol) and 1.1.17-1.61 eV (PBE) (Lu et al, 2016;Sun P.-P. et al, 2016;Zhao Y.-Q. et al, 2017) were reported for CH 3 NH 3 GeI 3 , and those of the hybrid functional range from 1.70 to 2.04 eV (Sun P.-P. et al, 2016;Zhao Y.-Q.…”
Section: Optical Propertiesmentioning
confidence: 95%
“…Next, we examine the influence of incorporated HS layer on the crystallinity in MAPbI 3 films using X‐ray diffractometry (XRD) and the results are displayed in Figure e. For MAPbI 3 prepared on HS/TiO 2 films, we observe a resembling crystal structure to that on bare TiO 2 with the (110), (220), and (310) diffraction peaks occurring at 14.1°, 28.2°, and 31.8°, respectively, in consistence with the major lattice structure of CH 3 NH 3 PbI 3 . All XRD peaks become intensified and sharper in the HS‐containing sample.…”
Section: Photovoltaic Device Parameters Of the Best Mapbi3 Solar Cellmentioning
confidence: 97%
“…105 Spin–orbit coupling effects were not considered here as they have been shown to be negligible in germanium-based hybrid perovskites. 58,59 The Brillouin zone and the high symmetry points used to generate band structures are taken from the handbook of Bradley and Cracknell. 106 The optical absorption spectrum was computed by using the transversal approximation and PAW method, which sums the absorption spectra over all direct valence band (VB)-to-conduction band (CB) transitions and therefore ignores indirect and intraband absorption, which, despite ignoring excitonic effects, has given reasonable optical absorption spectra 70,9398 and revealed if transitions are symmetry-allowed.…”
Section: Computational Methodsmentioning
confidence: 99%